Cooperative Control of Nonlinear Networked Systems Infinite-time and Finite-time Design Methods - Song, Yongduan; Wang, Yujuan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Cooperative Control of Nonlinear Networked Systems is concerned with the distributed cooperative control of multiple networked nonlinear systems in the presence of unknown non-parametric uncertainties and non-vanishing disturbances under certain communication conditions. It covers stability analysis tools and distributed control methods for analyzing and synthesizing nonlinear networked systems. The book presents various solutions to cooperative control problems of multiple networked nonlinear systems on graphs. The book includes various examples with segments of MATLAB® codes for readers to verify, validate, and replicate the results. The authors present a series of new control results for nonlinear networked systems subject to both non-parametric and non-vanishing uncertainties, including the cooperative uniformly ultimately bounded (CUUB) result, finite-time stability result, and finite-time cooperative uniformly ultimately bounded (FT-CUUB) result. With some mathematical tools, such as algebraic graph theory and certain aspects of matrix analysis theory introduced by the authors, the readers can obtain a deeper understanding of the roles of matrix operators as mathematical machinery for cooperative control design for multi-agent systems. Cooperative Control of Nonlinear Networked Systems is a valuable source of information for researchers and engineers in cooperative adaptive control, as its technical contents are presented with examples in full analytical and numerical detail, and graphically illustrated for easy-to-understand results. Scientists in research institutes and academics in universities working on nonlinear systems, adaptive control and distributed control will find the book of interest, as it contains multi-disciplinary problems and covers different areas of research.
Chapter 1. Introduction -- Chapter 2. Preliminaries -- Chapter 3. Lyapunov Analysis for Cooperative Adaptive Consensus under Undirected Graph -- Chapter 4. Cooperative Adaptive Consensus Control for Uncertain Multi-agent Systems with nth-Order Dynamics under Undirected Graph -- Chapter 5. Cooperative Adaptive Consensus for Multi-Agent Systems under Directed Topology -- Chapter 6. Finite-time Leaderless Consensus Control for Systems with First-Order Uncertain Dynamics -- Chapter 7. Finite-time Consensus for Systems with Second-Order Uncertain Dynamics under Undirected Topology -- Chapter 8. Finite-time Consensus for Systems with Second-Order Uncertain Dynamics under Directed Topology -- Chapter 9. Finite-time Leaderless Consensus Control for Systems with high-Order Uncertain Dynamics.
Keywords: Control engineering; System theory; Control theory; Telecommunication; Computer networks .; Control and Systems Theory; Systems Theory, Control; Communications Engineering, Networks; Computer Communication Networks